2022
DOI: 10.3390/plants11212853
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Spermidine Promotes Germination of Aged Sorghum Seeds by Mediating Sugar Metabolism

Abstract: Starch, a substance stored in seeds, is the main source of energy for germination in sorghum seeds. However, as the seeds age, the catabolism of seed starch is affected, thereby seriously damaging germination ability. In this study, we aimed to understand how exogenous spermidine promoted germination in aged sorghum seed. Our phenotypic analysis indicated that exogenous spermidine not only significantly improved the germination rate, germination potential, germination index, and vigor index of aged seeds, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Moreover, research has shown that CSN improves germination and seedling establishment in aged sunflower seeds by increasing FA conversion into sucrose [ 12 ]. Another study found that exogenous spermidine promotes sorghum seed germination by promoting starch and sugar utilization [ 10 ]. As safflower is an essential economic crop that relies on high-quality seeds for efficient and effective plant production, the ability to enhance germination in aged seeds potentially has huge implications for agriculture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, research has shown that CSN improves germination and seedling establishment in aged sunflower seeds by increasing FA conversion into sucrose [ 12 ]. Another study found that exogenous spermidine promotes sorghum seed germination by promoting starch and sugar utilization [ 10 ]. As safflower is an essential economic crop that relies on high-quality seeds for efficient and effective plant production, the ability to enhance germination in aged seeds potentially has huge implications for agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Germination was recorded after seven days with germination defined as radicle emergence by >2mm. The parameters of germination that were determined were [ 10 ]: Germination rate = the number of normally germinated seeds on the 7th day/the total number of tested seeds × 100% Germination potential = the number of normally germinated seeds on the 2nd day/the total number of tested seeds × 100% Germination index = ∑(Gt/Dt) where Gt is the number of germinations on the 7 days; Dt is the number of germination days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future work will be needed to determine whether the changes in the endogenous levels of starch may be linked to altered VQ10 gene expression and to phenotypes such as altered root growth or sensitivity to nitroxidative stress described in this article. However, starch that is stored in seeds, is the main source of energy for germination and it was documented that the starch content affect seed germination through alterations in the starch‐sugars balance due to altered starch metabolism (Zhang et al, 2022). We checked whether the energy status of plants with enhanced VQ10 expression was significantly different from wild‐type plants either under non‐stressed conditions or upon nitroxidative stress caused by application of exogenous NO.…”
Section: Discussionmentioning
confidence: 99%